The Role of Business Feasibility Studies in Distribution Business Expansion at PT XYZ Logistik - Okis Kumaladani; Raden Johnny Hadi Raharjo (Jurnal Paradigma, 2026)
This study analyzes the role of business feasibility studies in supporting the expansion of a logistics company’s distribution network in Balikpapan, East Kalimantan. The research is motivated by the rapid infrastructure development in Indonesia, particularly in the IKN area, which has significantly increased cement demand and created a gap in distribution capacity. Employing a descriptive qualitative approach, data were collected through in-depth interviews, internal documentation, and literature review. The findings reveal that business feasibility studies function as a strategic instrument that integrates analyses of market, technical-operational, management and human resources, financial, and legal aspects. Market and financial aspects are identified as the dominant factors in determining expansion feasibility, while technical, managerial, and legal aspects serve as supporting factors that ensure operational readiness and regulatory compliance. This study contributes to the development of feasibility study literature by emphasizing that in the cement distribution industry, characterized by high logistical complexity, expansion decisions are driven by the rational integration of market opportunities and the company’s financial capacity, thereby providing strategic implications for the sustainability of corporate operations.